2014
DOI: 10.3389/fnbeh.2014.00106
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic learning and memory, synaptic plasticity and neurogenesis: an update

Abstract: Mammalian memory is the result of the interaction of millions of neurons in the brain and their coordinated activity. Candidate mechanisms for memory are synaptic plasticity changes, such as long-term potentiation (LTP). LTP is essentially an electrophysiological phenomenon manifested in hours-lasting increase on postsynaptic potentials after synapse tetanization. It is thought to ensure long-term changes in synaptic efficacy in distributed networks, leading to persistent changes in the behavioral patterns, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
89
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(89 citation statements)
references
References 75 publications
0
89
0
Order By: Relevance
“…The expression of the brain-derived neurotrophic factor was also found to be increased in the hippocampus, 15 which is an area associated with memory and learning. 20 …”
Section: Introductionmentioning
confidence: 99%
“…The expression of the brain-derived neurotrophic factor was also found to be increased in the hippocampus, 15 which is an area associated with memory and learning. 20 …”
Section: Introductionmentioning
confidence: 99%
“…Learning triggers neuronal changes in the brain that contribute to information acquisition and memory formation, including the activity and strength of existing synapses, the formation of new synapses, and possibly the birth of new neurons (1). Therefore, it is not surprising that neurons have been seen as the sole components of the nervous system, capable of responding to experience and responsible for learning and long-term behavioral plasticity.…”
Section: The Adult Mammalian Brain Requires the Production Of New Glimentioning
confidence: 99%
“…Moreover, it has been shown that melatonin also affects the firing rate of hippocampal CA1 neurons [6] and the appearance of circadian hormonal modulation of neuronal firing as a general mechanism throughout the brain has been revealed [7].…”
Section: Introductionmentioning
confidence: 99%